Institutions, Human Capital, and Long-Run Growth : An Empirical Assessment of the Augmented Solow Framework - Vykouk, Jan; Kotrba, Vojtěch; Kouba, Luděk; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines the Solow growth model and its extensions with human capital and institutional quality, assessing their relevance for long-term economic growth and income convergence. The analysis also applies the Ball and Mankiw (2023) dynamic efficiency criterion to the Czech Republic. The Czech economy is found to be dynamically efficient. Cross-country evidence shows that Kaldor’s stylized facts no longer hold universally, while the capital-output ratio remains relatively stable with a slight upward trend, the capital share of output has increased over time. Cross-sectional regressions for 1971–2019 and 2003–2019 provide evidence of absolute convergence, although its magnitude is low. The inclusion of human capital and institutional variables decreases the estimated capital share and increases the speed of convergence, and these findings are robust across both time periods. Institutional quality is measured using six proxies, government effectiveness, regulatory quality, rule of law, control of corruption, voice and accountability, and political stability. Panel estimations using system GMM provide the most robust evidence. The augmented model yields a convergence speed of 0.067 with a capital share of 0.50, the inclusion of institutional variables raises the convergence speed to 0.097 (government effectiveness) and 0.092 (regulatory quality) and reduces capital shares to 0.39 and 0.35, respectively. These results identify human capital and institutional quality as central determinants of long-run growth and essential for explaining cross-country income convergence.
Vedoucí práce: Vojtěch Kotrba
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses